HUBUNGAN PENGETAHUAN DENGAN SIKAP REMAJA TENTANG KESEHATAN REPRODUKSI DI SMPN 14 TAKENGON - -, Yulia Ernida (Jurnal Ilmiah Kesehatan Ibu dan Anak, 2023)
The influence of global information (exposure to audio-visual media) which is increasingly accessible actually provokes children and adolescents to adopt unhealthy habits that cause many problems for adolescent reproductive health. Many problems would arise as a result of neglecting reproductive health. The aim of this study was to find out whether there is a relationship and attitudes of adolescents about reproductive health at SMPN 14 Takengon. This study used an analytical method with a cross-sectional approach. Sampling was carried out in a non-probability manner with the accidental sampling method, from the research results obtained a total sample of 48 respondents. Research instrument using a questionnaire. Data processing were carried out using editing, coding, entry and cleaning. Data analysis used was bivariate analysis. The results of this study showed that there was a relationship between knowledge and attitudes of adolescents towards reproductive health at SMPN 14 Takengon with a confidence level of 95% (α 0.05), it was known that the p value is 0.004 meaning that the p value is 0.004 ≤ 0.05 Chi-square test.